Book Review: Mindy Kay Bricker (Ed.), The Fukushima Daiichi Nuclear Power Disaster: Investigating the Myth and Reality. (September 2014) - Atkinson, Christopher L.
Mindy Kay Bricker (Ed.), The Fukushima Daiichi Nuclear Power Disaster: Investigating the Myth and Reality, by the Independent Investigation Commission on the Fukushima Nuclear Accident (1st ed.). Abingdon, Oxon and New York: Earthscan/Routledge, 2014, 298 pp. (ISBN: 978-0-415-71393-1 [HB, US$ 145]; 978-0-415-71396-2 [PB, US$ 39.95])